Rapid Turnover of Hepatitis B Virus Covalently Closed Circular DNA Indicated by Monitoring Emergence and Reversion of Signature‐Mutation in Treated Chronic Hepatitis B Patients. Issue 1 (1st December 2020) - Huang, Qi; Zhou, Bin; Cai, Dawei; Zong, Yuhua; Wu, Yaobo; Liu, Shi; Mercier, Alexandre; Guo, Haitao; Hou, Jinlin; Colonno, Richard; Sun, Jian
Abstract : Background and Aims: Hepatitis B virus (HBV) covalently closed circular DNA (cccDNA) plays a pivotal role in the establishment and persistence of HBV infection. Understanding the turnover time of preexisting cccDNA pools would be helpful in designing strategies to clear HBV by fully blocking the de novo generation of cccDNA. Approach and Results: In this study, we retrospectively monitored the emergence and reversion of the rtM204I/V mutant, a signature lamivudine resistance (LAM R ) mutation serving as a biomarker of cccDNA turnover in liver biopsies and longitudinal serum samples from two clinical trials. Methodologies were optimized to differentially isolate and sequence HBV virion DNA, cccDNA, and HBV RNA from clinical samples. A strong correlation was observed between LAM R composition of cccDNA with that of serum and intrahepatic HBV RNA in paired liver and serum samples (r = 0.96 and 0.90, respectively), suggesting that serum HBV RNA can serve as a surrogate marker of cccDNA genetic composition when liver biopsies are unavailable. LAM R mutations emerged and increased from undetectable to 40%‐90% within 16‐28 weeks in serum HBV RNA from telbivudine‐treated patients experiencing virological breakthrough. Similarly, in lamivudine‐resistant patients who switched to interferon therapy, serum HBV‐RNA population bearing 100% LAM R mutations fully reversed back to wild type within 24‐48 weeks. Conclusions: The genetic composition dynamics of serum HBV RNA and biopsy cccDNA in treated HBV patients indicates that cccDNA turnover occurs relatively rapidly (several months), offering a possibility of HBV cure with finite therapy through completely blocking cccDNA replenishment.